Out-of-body experiences - Blackmore, Susan (Parapsychology, 2005)
The best evidence supporting the belief in reincarnation comes from the cases of young children who, typically between the ages of 2 and 5, make statements about a previous life they claim to have lived before being born. Some sensitives claim to 'read' the previous lives of their clients, but what they say is nearly always banal, vague, and unverifiable. The same can be said of nearly all claims to regress persons with hypnosis to previous lives. Alternative interpretations besides reincarnation and faulty memory on the part of informants need to be considered in appraising individual cases. Haraldsson has conducted psychological tests on thirty children of Sri Lanka who claimed to remember previous lives compared with thirty other children of the same age, sex and background. Interpretations of the cases as due to paranormal cognition between the subjects and living persons who knew the concerned deceased person fail to account for all features of many cases.